Winning at war : seven keys to military victory throughout history - Potholm, Christian P., 1940- (Lanham, Md. : Rowman & Littlefield Publishers, 2010)
"Drawing on forty years of studying and teaching war, political scientist Christian P. Potholm presents a 'template of Mars' -- seven variables that have served as predictors of military success over time and across cultures. In Winning at war, Potholm explains these variables -- technology, sustained ruthlessness, discipline, receptivity to innovation, protection of military capital from civilians and rulers, will, and the belief that there will always be another war -- and provides case studies of their implementation, from ancient battles to today'"--Jacket.
Introduction: The template of Mars -- Superior weapons and technology entrepreneurship -- Superior discipline -- Sustained but controlled ruthlessness -- Receptivity to military and integrative innovation -- The ability and willingness to protect capital from people and rulers -- The centrality of superior will -- The belief there will always be another war -- Applying the template : a battle -- Applying the template : a war.
Includes bibliographical references and index.
Keywords: Military art and science -- History; Military art and science -- Case studies; Military art and science; Krieg; Geschichte; Case studies; History; Case studies